2007
DOI: 10.1002/ana.21115
|View full text |Cite
|
Sign up to set email alerts
|

β‐Amyloid is a substrate of autophagy in sporadic inclusion body myositis

Abstract: These findings indicate that APP/beta-amyloid is targeted for lysosomal degradation via macroautophagy and suggest that the autophagy pathway should be explored for its potential therapeutic merit in sIBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 21 publications
4
92
0
1
Order By: Relevance
“…However, it took another 24 years for evidence that members of the autophagy machinery ( Atg5 and Atg12 ) are upregulated on mRNA level in IBM muscle as compared to healthy and amyotrophic lateral sclerosis muscle 259. We demonstrated that accumulated APP and its proteolytic fragment A β in skeletal muscel fibers are targeted for lysosomal degradation via macroautophagy 260. We observed APP/A β ‐containing autophagosomes at increased frequency in muscle fibers of IBM muscle biopsies, but not in nonmyopathic muscle or nonvacuolated myopathic controls.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 89%
See 1 more Smart Citation
“…However, it took another 24 years for evidence that members of the autophagy machinery ( Atg5 and Atg12 ) are upregulated on mRNA level in IBM muscle as compared to healthy and amyotrophic lateral sclerosis muscle 259. We demonstrated that accumulated APP and its proteolytic fragment A β in skeletal muscel fibers are targeted for lysosomal degradation via macroautophagy 260. We observed APP/A β ‐containing autophagosomes at increased frequency in muscle fibers of IBM muscle biopsies, but not in nonmyopathic muscle or nonvacuolated myopathic controls.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 89%
“…We observed APP/A β ‐containing autophagosomes at increased frequency in muscle fibers of IBM muscle biopsies, but not in nonmyopathic muscle or nonvacuolated myopathic controls. Moreover, A β ‐containing autophagosomes were almost exclusively observed in degenerating muscle fibers of the type II (fast‐twitching) and in part associated with overexpression of MHC class I and II on myofibers and invasion by CD4 + and CD8 + cells 260. A more recent immunohistochemistry study reports overexpression of the autophagy proteins ATG5, microtubule‐associated protein light chain 3 (LC3) and Beclin‐1 in IBM muscle biopsies.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%
“…However, Ab 42 is more easily to aggregate than Ab 40 , so how Ab 42 drainage from neurons and serve as seeds nearby vessels was a question. One answer is that vessel itself might produce Ab 42 to act as seeds. This was important for the CAA formation because the local secreted Ab 42 could act as seeds to aggregate less fibrillogenic Ab 40 secreted nearby or drainage to the vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The level of Ab 42 generated from HUVEC after starvation and 3MA treatment was measured by enzyme-linked immunosorbent assay kit for Ab 42 (ELISA) (ExCell Bio, EH025). After starvation, medium was collected.…”
Section: Ab 42 Quantificationmentioning
confidence: 99%
See 1 more Smart Citation